Three-dimensional morphologies, substructures, and crystallography of pearlite in carbon steel - Akinobu Shibata; Akiko Nakamura; Taku Moronaga; Kazuho Okada; Toru Hara; Rintaro Ueji (Science and Technology of Advanced Materials)
The present study examined the morphology, substructure, crystallography, and element distribution of as-transformed (air-cooled) pearlite in medium-carbon steel using focused ion beam-scanning electron microscopy serial sectioning and advanced transmission electron microscopy analysis. The three-dimensional analysis revealed that the cementite did not exhibit a fully continuous lamellar structure, and the long axis direction of non-continuous region was nearly identical within each cementite lamella and among the adjacent cementite lamellae. The measured macroscopic interfacial plane orientation ranged from (0 1 0)θ to ([Formula: see text] 2 0)θ and ([Formula: see text] [Formula: see text] 5)α to ([Formula: see text] [Formula: see text] 1)α. The growth directions of cementite lamellae tended to align with the invariant line between cementite and ferrite, as well as the parallel direction in the Pitsch-Petch relationship. Even within a single colony, the orientations of both the ferrite and cementite regions changed discontinuously, forming low-angle boundaries, some of which exhibited a staircase-like shape. The orientation relationship between ferrite and cementite changed slightly at the low-angle boundary within a colony. This indicates that when the accumulated misfit strain exceeds a certain value, the parallel direction relationship changes to accommodate the accumulated strain while maintaining a nearly identical orientation relationship. The concentration inside cementite lamella was not completely homogeneous; manganese and chromium were enriched, while carbon was depleted, at the lamellar interface. We surmised that the inhomogeneous element distribution in cementite lamella could be attributed to the incomplete partitioning behavior of alloying elements at transformation, as well as their segregation at the lamellar interface, aiming to reduce interfacial energy.